Preparation of a supercapacitor electrode based on carbon nano-onions/manganese dioxide/iron oxide nanocomposite. (25th August 2022) - Sohouli, Esmail; Adib, Koroush; Maddah, Bozorgmehr; Najafi, Mostafa
Abstract: A facile synthesis of a new supercapacitor electrode based on carbon nano-onions/manganese dioxide/iron oxide (CNO/MnO2 /Fe3 O4 ) nanocomposite is reported in this work. Prepared nanomaterials were characterized by FE-SEM (field emission scanning electron microscopy), HRTEM (high-resolution transmission electron microscopy), XRD (X-ray powder diffraction), EDX (energy-dispersive X-ray), and FTIR (Fourier transform infrared spectroscopy). Characterization results greatly showed the successful synthesis of nanomaterials. A three-electrode system in sodium sulfate (0.5 M) was used to evaluate supercapacitor characteristics. Cyclic voltammetry experiments showed CNO/MnO2 /Fe3 O4 nanocomposite had a suitable supercapacitors property with a rectangular shape. The specific capacitance of electrodes prepared by MnO2, CNO, MnO2 /Fe3 O4, and CNO/MnO2 /Fe3 O4 calculated based on chronopotentiometry results were 202. 59, 340, 400 and 730 F/g at a current density of 4 A/g. A two-electrode symmetric supercapacitor was evaluated in which nanocomposite of CNO/MnO2 /Fe3 O4 was used as positive and negative poles. The specific capacitance, power density, and energy density calculated at a currency density of 4 A/g were 456 F/g, 160 Wh/kg, and, 400 W/kg, respectively. The value of capacitance obtained for the CNO/MnO2 /Fe3 O4 was obtained by the cyclic voltammetry method equal to 441.18 A/g (scan rate: 10 mV·s). Also, after 5000 consecutive cycles, it has decreased by about 17.76 % of the initial capacitance, which indicates that the electrode has good stability. A very low charge transfer resistance was concluded by electrochemical impedance spectroscopy. Highlights: Simple and cost-effective supercapacitor electrode based on CNO/MnO2 /Fe3 O4 was constructed. Excellent results were obtained in three and two electrodes systems. Good stability was achieved after 3000 consecutive cycles. The specific capacitance of prepared electrode was 730 F/g at a current density of 4 A/g.